2014
DOI: 10.1155/2014/630870
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Concentration in Platelet-Rich Plasma Affects Tenocyte BehaviorIn Vitro

Abstract: Since tendon injuries and tendinopathy are a growing problem, sometimes requiring surgery, new strategies that improve conservative therapies are needed. Platelet-rich plasma (PRP) seems to be a good candidate by virtue of its high content of growth factors, most of which are involved in tendon healing. This study aimed to evaluate if different concentrations of platelets in PRP have different effects on the biological features of normal human tenocytes that are usually required during tendon healing. The diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
77
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 54 publications
6
77
0
4
Order By: Relevance
“…Yamaguchi et al 34 showed PRP concentration had a dose-dependent effect on intestinal anastomotic healing in rats, where a lower PRP platelet concentration (2 000 000/µL) exerted positive effects, while the higher PRP platelet count (5 000 000/µL) was harmful to healing. A second study by Giusti et al demonstrated positive effects on human tenocyte proliferation using a concentration of 500 000 and 1 000 000/µL while again 5 000 000/µL induced cell death 35. There currently is not a consensus for an optimal PRP dose, but further clinical studies will hopefully identify therapeutic dose ranges for particular indications.…”
Section: Discussionmentioning
confidence: 99%
“…Yamaguchi et al 34 showed PRP concentration had a dose-dependent effect on intestinal anastomotic healing in rats, where a lower PRP platelet concentration (2 000 000/µL) exerted positive effects, while the higher PRP platelet count (5 000 000/µL) was harmful to healing. A second study by Giusti et al demonstrated positive effects on human tenocyte proliferation using a concentration of 500 000 and 1 000 000/µL while again 5 000 000/µL induced cell death 35. There currently is not a consensus for an optimal PRP dose, but further clinical studies will hopefully identify therapeutic dose ranges for particular indications.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, comparison of different platelet concentrations in PRP showed in vitro that rates of 2.5 fold gave better results on fibroblast and osteoblast proliferation and functionality [46]. In contrast, a recent in vitro study aimed to evaluate the effects of different platelet concentrations in PRP on the biological features of normal human tenocytes, which are usually required during tendon healing, suggests the need for a compromise between extremely high and low platelet concentrations to obtain an optimal global effect when inducing in vivo tendon healing [48].…”
Section: Collection and Preparationmentioning
confidence: 99%
“…Selon [4][5][6] ; une concentration supérieure à 1200 000 plaquettes pourrait effectivement s'avérer néfaste [6][7][8]. On devrait pouvoir injecter un PRP reproductible (concentration plaquettaire identique) chez tous les patients [9].…”
Section: Préparation Du Prpunclassified